PENINGKATAN EFIKASI DIRI PASIEN HIPERTENSI DENGAN METODE PEER GROUP SUPPORT - Oktavianisya, Nelyta; Aliftitah, Sugesti (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2024)
Self-efficacy or an individual's belief in their ability to manage their health condition is very important in the management of hypertension. In patients with hypertension, self-efficacy affects how well they can implement the changes needed to control blood pressure. Patients who have high levels of self-efficacy tend to be better able to follow the treatment plan and are more proactive in changing risky lifestyle habits. Psychological factors, such as anxiety and depression, as well as social support from family and friends, can affect the level of self-efficacy. Peer Group Support is one method that can be done in an effort to increase the self-efficacy of hypertensive patients, namely through behavioral modeling, emotional support, shared experiences, constructive feedback, goal setting, skill development, role models and stress reduction. The purpose of the study was to determine the effect of peer group support on the self-efficacy of hypertensive patients. The research design was pre-experimental. The sample in this study was part of the hypertensive patients, namely 42 respondents. Simple random sampling is the sampling technique used. The tool used to measure self-efficacy is a questionnaire. Data were processed using the Paired Samples T Test. The average value of self-efficacy before the intervention (pre) was 66.12 with a standard deviation of 7.006. The average value of self-efficacy after the intervention (post) increased to 75.64 with a standard deviation of 7.870. The results of the pretest-posttest self-efficacy data analysis using the Paired Samples T Test obtained a value of ?Value = 0.000 with ? = 0.05. Because ?Value <?, there is an influence of peer group support on self-efficacy in hypertension patients. It is hoped that health workers will plan routine activities that involve fellow patients. Where hypertension patients can strengthen each other, share information and convince fellow patients to improve their quality of life